Crew Resource Management and Communication - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Communication is one of the few unbounded topics with several definitions and applications as it is so central to human endeavour. Communication is an integral part of the social sciences, whether printed, verbal or non-verbal, remote or face-to-face: political science, anthropology, sociolinguistics, psychology, etc. Beyond conventional scholars, conversation is pragmatic; that is to say, people interact to gain what we need and achieve goals. In this paper, researchers demonstrates about the communication in terms of success; people are confused or understood, knowledge is transmitted or not; they are either unmoved or convinced. Communication skills helps determining the failure or success of achieving goals, and communication efficiency becomes important when one's ambitions are added to the high stakes.